Assessment of total columnar ozone climatological trends over the Indian sub-continent. Issue 12 (18th June 2018) - Pathakoti, Mahesh; Asuri, Lakshmi Kanchana; Dangeti Venkata, Mahalakshmi; Peethani, Sujatha; Gaddamidi, Sreenivas; Soni, Vijay Kumar; Peshin, Sunil Kumar
ABSTRACT: In the present study, long term satellite and Dobson spectrophotometer Total Column Ozone (TCO) data have been used to study the interannual variability and also to assess climatological trends in TCO over different geographical locations of Indian sub-continent. TCO data were analyzed for the period 1957 to 2015 over New Delhi (28.63° N, 77.18° E), Varanasi (25.30° N, 83.02° E), Pune (18.53° N, 73.84° E) and Kodaikanal (10.0° N, 77.47° E). An extensive validation was performed for Total Ozone Mapping Spectrometer (TOMS) and Ozone Monitoring Instrument (OMI) retrieved TCO data independently with Dobson Spectrophotometer TCO measurements over New Delhi, Varanasi, Pune and Kodaikanal. The results of this exercise showed good correlation coefficient ( r ) of 0.87 (0.88), 0.84 (0.82), 0.91 (0.80) and 0.84 (Data not available) respectively. Climatological mean TCO over New Delhi, Varanasi, Pune and Kodaikanal are 275.02 ± 6.44 DU, 269.03 ± 7.34 DU, 260.78 ± 5.07 DU and 258.71 ± 6.36 DU respectively for the period 1957 to 2015. An increasing trend over New Delhi (0.20 DU year –1 ), Pune (0.18 DU year –1 ), Kodaikanal (0.14 DU year –1 ) and decreasing trend over Varanasi (0.01 DU year –1 ) were observed. High significance of TCO trend was found at New Delhi ( p -value < 0.0001), Pune ( p -value = 0.002) and Kodaikanal ( p -value = 0.003) with negligible trend over Varanasi with p -value of 0.84. The TCO variations at different geographical locations associated with upper atmospheric meteorological parameters such as lower Stratospheric Temperature (ST) at 65 hPa and Tropopause Height (TH) were also addressed. Annual lower stratospheric temperature shows positive relationship with TCO and Stratospheric ozone over the study sites. Further, decadal variability in TCO with respect to solar activity at New Delhi was also analyzed.